Fettered to Gold? Economic Policy in the Interwar Period - Cooper, Richard N. (Journal of Economic Literature, 1992)
for at least three reasons. First, it is fun. A skillful narrator and analyst can bring alive exciting or important events, and that is enjoyable. Second, a study of history alerts economists to two important but usually neglected characteristics of economies, namely that they are sometimes strongly influenced by noneconomic factors-not only wars, but political impasses, charismatic leaders, or ideological beliefs deeply rooted in public or official psychology-and that contrary to what is usually assumed in formal modeling, the structure of economies changes over time as public attitudes change and as institutions evolve. Third, economists should study history, at least relatively recent history, because it is usually impossible to understand our institutions and attitudes without some appreciation of the events that shaped the legacy from our parents and grandparents. Barry Eichengreen has written a book that is likely for some time to become the standard reference on monetary and financial developments during the interwar period, 1919-1936.' It is traditional history, telling a story, or rather a series of stories, with more tables and charts and a stronger reliance on economic concepts than most histories, but little econometrics and no formal modeling. The interwar period, which contains what is still the most dramatic and traumatic economic event of the past century, the Great Depression, left a strong imprint on contemporary American, European, and world institutions and attitudes, such as the Securities and Exchange Commission, the Glass-Steagall Act requring the separation of banking from other activities, and the International Monetary Fund. In addition to telling an interesting story, Eichengreen helps us interpret those events in ways that may have lessons for the future as well. Eichengreen's most significant conclusion is that the Great Depression was due to attempts to adhere to a restored gold standard with inadequate international cooperation to make it work. That flawed behavior, in turn, must be understood in light of experience in the early 1920s, especially in three critical countries-France, Germany, and the United States. As the interwar period may not be well known to most readers of this Journal, I first sketch the main economic and political events. The next section indicates the influence of these events on post-World War II international institutions and behavior. I turn then to the various explanations that have been put forward for the severity of the Great Depression, and conclude with a commentary on Eichengreen's contribution to this literature, and to our understanding of the interwar period more generally.